Math, asked by aliwaran70, 5 months ago

9х – 5у = 2
3х - 4 y = 10
By elimination method

Answers

Answered by bounty9hunter
0

Answer:

x= -2          y = -4

Step-by-step explanation:

9 x - 5 y = 2        multiply whole expression by 1

3 x - 4 y = 10          multiply whole expression by 3

9 x - 5 y = 2    equation 1

9 x - 12 y = 30     equation 2

subtract equation 2 from equation 1

7 y = -28

y = -4

Substitute y into either 9 x - 5 y = 2 or 3 x - 4 y = 10

9 x +20=2                                  3 x + 16 = 10  

9 x=-18                                              3 x = -6

x= -2                                                  x= -2

Answered by hekittu224
0

Answer:

good answer 100℅ correcct

Similar questions